Hubungan Antara Ekspresi yclooxygenase-2 Dan Reseptor Estrogen Dengan Derajat Histologis Dan Stadium Karsinoma Payudara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Irianiwati, Abraad Ghorali, Stefanus Yoanito The correlation between cycioexygenase-2 expression and estrogen reseptor expression with histological grade and stage of breast cancer Background: Cyclooxygenase-2 (00X-2I is a key enzyme in the coaersion of arachldonic acid to prostaglandin. Prostaglandin increase expression and activation, which is the enzyme that produces estrogen {ER) from androgen. Estrogen can increase breast cancer tumor cell growth via activation of the estrogen receptor and its target genes. In breast cancer, the role of COX-2 and estrogen raseptor {ER) relates to clinical stage and histological grade have not been defined yet. Methods: Fifty cases of breast cancer paraffin blok were determined its size, lymphnode metastasis, stage and histological grade. All of the specimens were stained immunobistochemically with streptavidin biotin complex method, using monoclonal antibody of COX-2 and ER were counted based on the number of positives calls/100 tumor cells In five microscopic fields. Results: There was a significant correlation between COXâ¢2 expression and histological grade of breast cancer fr: 0.665